Analisis Kinerja dan Reduksi Emisi Karbon pada Mesin Pemipil Jagung Berbasis Energi Surya - Toni Okviyanto; Hendradinata Hendradinata; Firdaus Firdaus; Tri Satya Ramadhoni; Agis Fika Wulandari; Indra Syahputra; Stevan Juliandro Aruan (Infotekmesin, 2026)
Agricultural post-harvest operations require technological innovations that enhance productivity while reducing dependence on fossil fuels and environmental impacts. Although solar energy has been increasingly applied in agricultural mechanization, previous studies have primarily focused on technical performance or energy consumption, with limited attention to integrating machine performance evaluation and carbon emission reduction. This study aimed to evaluate the performance of a solar-powered corn sheller and assess its carbon emission reduction potential compared with a gasoline-powered sheller. A comparative experimental method was employed by analyzing shelling capacity, shelling efficiency, energy consumption, kernel damage, and carbon emissions using the Intergovernmental Panel on Climate Change (IPCC) emission factor. The results showed that the solar-powered sheller achieved a shelling capacity of 65 kg h⁻¹ and a shelling efficiency of 90%, which were comparable to the gasoline-powered sheller (69.67 kg/h and 91.67%, respectively). Moreover, the solar-powered system produced no direct operational carbon emissions, whereas the gasoline-powered sheller emitted 0.5082 kg CO₂ per 10 kg of processed corn. The novelty of this study lies in integrating technical performance evaluation with IPCC-based carbon emission analysis. This study provides a comprehensive evaluation framework to support the development of low-carbon agricultural mechanization based on renewable energy.